In Search of Identity: The Contemporary Islamic Communities in Southeast Asia - Hasan, Noorhaidi (Studia Islamika, 2000)
The primary objective of this paper is to investigate the contribution of contemporary Islamic movements to the rise of the public sphere in Southeast Asia, particularly in Indonesia and Malaysia. Implicit in this idea of "contribution" is the empowerment of Muslims as once disenfranchised groups within the context of the development of civil society. This analysis includes consideration of the following movements: The most phenomenal "Darul Arqam", a Kuala Lumpur-based movement that was banned by the South-East Asian authorities in mid 1994. With its own characteristics, "JIM (Malaysian Reformation Community)" is also interesting to study within the context of the political transformation of Malaysia. In the case of Indonesia, we encounter such contemporary movements as "Jamaah Hidayatullah" and "Darut Tauhid", two movements that exhibit a strong desire to empower Muslims in the social and economic realms. There is also a religious community known as "Jamaah Al-Turath al-Islami", that tends to with draw from the public sphere, yet maintains some hope to play a role in the political arena at some point.DOI: 10.15408/sdi.v7i3.703